Inhomogeneous charge states and electronic transport in manganites (Review Article): - Kagan, M. Yu.; Kugel, K. I.; Rakhmanov, A. L.; Khomskii, D. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We analyze the interplay between charge ordering, magnetic ordering, and the tendency toward phase separation and its importance for the physics of manganites. A simple model of charge ordering isconsidered. It takes into account both the Coulomb repulsion at neighboring sites responsible for charge ordering and the essential magnetic interactions. It is shown explicitly that at any deviation from half-filling (n¹1/2) the system is unstable with respect to phase separation into charge-ordered regions with n=1/2 and metallic regions with smaller electron or hole density. A possible structure of this phase-separated state (metallic droplets in a charge-ordered matrix) is discussed. We construct the phase diagram reproducing the main features observed in real manganites. Based on the same physical picture,we also derive explicit expressions for the dc conductivity and noise power in the phase-separated state. It is shown that the noise spectrum has nearly 1/f form in the low-frequency range.